The Impact Imposed by Brand Elements of Enterprises on the Purchase Intention of Consumers—With Experience Value Taken as the Intermediary Variable - Zong, Yi; He, Menghui (Frontiers in Psychology, 2022)
Against the backdrop of China’s current dual-circulation paradigm, consumers have experienced the transition of their demands for products from the price-driven needs to the brand-driven needs. On the one hand, improving the value of consumer experience during brand building can enhance the exchanges and interactions between brands and consumers, facilitating the co-creation of value. On the other hand, the improvement of consumer experience can continuously strengthen the internal power of the construction of enterprise brand elements, and promote consumer brand identity so as to constantly improve consumer purchase intention. In this study, we have taken consumers in the B2C market as the survey group while innovatively studying the impact imposed by brand elements on the purchase intention of consumers based on the experience value. In addition, we have established the theoretical framework of brand elements—experience value—consumers’ purchase intention based on our analysis on the relationship on the aforementioned three factors. Through empirical research, we have elaborated on whether brand elements can improve consumers’ purchase intention and whether the experience value can play an intermediary role. The research findings indicate that: (1) The three dimensions of brand elements, namely, brand personality, brand value and brand culture can impose significant positive impact on the purchase intention of consumers and experience value; (2) The specific parts of the experience value, namely, functional value, emotional value, social value and service value, can impose a significant positive impact on the purchase intention of consumers; and (3) Experience value can play an intermediary effect to some extent while brand elements are influencing the purchase intention of consumers.